WHAT IS IN A NAME? CHARACTERISING THE 'POST-HOWIESON'S POORT' AT SIBUDU - (:unkn) unknown (My University, 2012)
Since the recognition in the 1980s and 1990s that modern humans originated in Africa, studies of the Middle Stone Age (MSA) have moved from obscurity to a central topic for defining the cultural adaptions that accompanied the advent and spread of modern humans. Much of recent research in southern Africa has focused on Still Bay and Howieson's Poort assemblages, and these industries have often been viewed as central to our understanding of cultural evolution during the MSA. As part of the process of correcting this bias, we examine lithic assemblages from Sibudu Cave in KwaZulu-Natal where there are deep and archaeologically rich strata with ages of c. 58 ka. We argue that the 'post-Howieson's Poort' forms a coherent entity with a clear technological signature. We suggest that detailed studies of technology and subsistence and settlement dynamics at Sibudu can provide important information on human adaptations and provide key data to help researchers gain a better understanding of cultural evolution during the MSA. From this point of view Sibudu can serve as a type site for characterising what has informally been referred to as the post-Howieson's Poort. Future work will help to define the spatial-temporal distribution and the variability of what we have called the Sibudu assemblage type in the Stone Age prehistory of KwaZulu-Natal and within southern Africa. The first step in this process is to characterise the key elements of the post-Howieson's Poort lithic technology documented at Sibudu.
Keywords: African Research